2014
DOI: 10.1093/bioinformatics/btu032
|View full text |Cite
|
Sign up to set email alerts
|

jmodeltest.org: selection of nucleotide substitution models on the cloud

Abstract: Summary: The selection of models of nucleotide substitution is one of the major steps of modern phylogenetic analysis. Different tools exist to accomplish this task, among which jModelTest 2 (jMT2) is one of the most popular. Still, to deal with large DNA alignments with hundreds or thousands of loci, users of jMT2 need to have access to High Performance Computing clusters, including installation and configuration capabilities, conditions not always met. Here we present jmodeltest.org, a novel web server for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 4 publications
0
64
0
Order By: Relevance
“…This program uses a Phi-test of recombination (Bruen et al 2006) to find evidence supporting recombination. An analysis by jModelTest 2 (Darriba et al 2012) showed that models with gamma distribution and invariant sites offered the best fit to the data under both the Akaike and the Bayesian information criteria for the nrITS and the rpL16 regions. MrBayes v3.2 (Ronquist et al 2012) was used for the phylogenetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…This program uses a Phi-test of recombination (Bruen et al 2006) to find evidence supporting recombination. An analysis by jModelTest 2 (Darriba et al 2012) showed that models with gamma distribution and invariant sites offered the best fit to the data under both the Akaike and the Bayesian information criteria for the nrITS and the rpL16 regions. MrBayes v3.2 (Ronquist et al 2012) was used for the phylogenetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…) as well as with Jmodeltest (Santorum et al. ) for nucleotides and ProtTest3 (Darriba et al. ) for amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…The 16S rRNA gene sequences from 2 clones of 10 cultured TRLO isolates (GenBank accession numbers KX691419−KX691438), a cultured New Zealand isolate identified in genome sequence assembly data (NZ-RLO; see BioProject accession number PRJNA 314275; Contig LVCQ01000264) (Gias et al 2016 Santorum et al 2014). For BI, trees were constructed using the K80 substitution model, calculating remaining parameters under the default prior distributions and employing the Monte Carlo Markov chain method (nchains = 4) over 4 000 000 generations, with every 200 th tree being saved.…”
Section: Dna Extraction Pcr Amplification and Phylogenetic Analyses mentioning
confidence: 99%
“…The alignment was verified by eye and then subjected to phylogenetic tree searches using Bayesian inference (BI) with MrBayes v.3.2.2 (Huelsenbeck & Ronquist 2001), maximum likelihood (ML) with RAxML v.8.0.24 (Stamatakis 2014) and maximum parsimony (MP) with PAUP* v.4.0 beta (Wilgenbusch & Swofford 2003). For the BI and ML analyses, the K80 nucleotide substitution model (Kimura 1980) was selected using the Bayesian Information Criteria test in jModeltest v.2.1.6 (Santorum et al 2014). For BI, trees were constructed using the K80 substitution model, calculating remaining parameters under the default prior distributions and employing the Monte Carlo Markov chain method (nchains = 4) over 4 000 000 generations, with every 200 th tree being saved.…”
Section: Dna Extraction Pcr Amplification and Phylogenetic Analyses mentioning
confidence: 99%
See 1 more Smart Citation